Dari kritik ke kriminalisasi: Analisis hakikat dan majaz terhadap ujaran sarkasme kepada pemerintah dalam Pasal 27 ayat (3) UU ITE - Fazri, Muhammad Ashabil (Maliki Interdisciplinary Journal, 2026)
Freedom of speech is a constitutional right guaranteed by Article 28E paragraph (3) of the 1945 Constitution of Indonesia, yet in practice it is frequently threatened by the application of Article 27 paragraph (3) of the Electronic Information and Transactions Law (UU ITE), which is widely criticized for its ambiguous and multi-interpretable provisions. A growing phenomenon in Indonesian legal practice is the criminalization of sarcastic utterances directed at the government or public officials, wherein law enforcement authorities often interpret criticism wrapped in sarcasm as defamation or insult. This article examines the issue from the perspective of Arabic rhetorical science (balaghah), specifically the concepts of haqiqah (literal meaning) and majaz (figurative meaning), as an analytical framework to dissect the linguistic nature of sarcastic speech. Haqiqah refers to the literal meaning of a word, while majaz denotes the use of a word in a non-literal sense, marked by context and qarinah (contextual indicators). Through a juridical-normative and linguistic analysis approach, this article argues that sarcasm is essentially a form of majaz that must not be interpreted literally. The criminalization of sarcastic utterances directed at the government not only contradicts principles of freedom of expression but also reflects a hermeneutic crisis in legal interpretation that fails to comprehend the linguistic dimension in its entirety. The article concludes that clear linguistic interpretation guidelines are urgently needed in the application of Article 27 paragraph (3) of the UU ITE to prevent it from becoming an instrument to silence legitimate public criticism of the government.